Predictive accuracy of triage nurses evaluation in risk stratification of syncope in the emergency department. Issue 11 (9th August 2013) - Bonzi, M; Fiorelli, E M; Angaroni, L; Furlan, L; Solbiati, M; Colombo, C; Dipaola, F; Montano, N; Furlan, R; Costantino, G
Abstract : Background: Syncope is a common clinical problem that accounts for 1–3% of all emergency department (ED) visits. Its prognosis is extremely variable with a 1-year mortality that may reach 30%. There are no available data about the accuracy of nursing triage in identifying high-risk syncope. The aim of our study was to evaluate the predictive accuracy of nursing triage in identifying high-risk syncope. Methods: We conducted a retrospective study on 678 consecutive patients who presented with syncope at four EDs. For each patient, nursing triage, comorbidities, clinical features and adverse events that occurred both in the ED and at 10-day follow-up were assessed. Adverse events included death, readmission to ED, need for major therapeutic procedures, cardiopulmonary resuscitation, intensive care unit admittance, acute antiarrhythmic therapy and major causes of syncope identified during the ED evaluation. Predictive accuracy of nursing triage was evaluated. Results: We observed a total of 55 (8.1%) adverse events. Eight of them (9.4%) occurred among the 85 patients who were identified as high priority by nursing triage. Sensitivity (Sn) and specificity (Sp) of urgent nursing triage in identifying adverse outcomes in the ED (19 patients) were 21% (95% CI 3% to 39%) and 88% (95% CI 85% to 90%), while the positive likelihood ratio (LR+) and negative likelihood ratio (LR−) were 1.7 and 0.9, respectively. Sn and Sp for 10-day adverse events were 15% (95% CI 5% to 24%) and 88% (95% CI 85% to 90%), respectively, with a LR+ of 1.18 and a LR− of 0.98. Conclusions: Nursing triage was characterised by a low predictive accuracy in identifying high-risk individuals.